Draft 7th Five Year Plan 1985-90 and Annual Plan 1985-86 Vol. V Jammu and Kashmir Government - Planning Commission (Planning Commission, 1984)
Rapid expansion of irrigation is a central element in agricultural strategy for the 7th plan and also the strategy for elevation poverty. Irrigation development in 7th plan will have to be passed on quick completion of on-going schemes, rapid utilisation of potential and better water management.
Planning and Development Department, Jammu and Kashmir Government